Description of a new species of the Liolaemus elongatus group (Squamata: Iguania) through integrative taxonomy - Ruiz, Soledad (2023)
Liolaemus is the genus with the highest number of lizard species described in South America up to date, with approximately 290. One of the groups within the genus, the Liolaemus elongatus group, is distributed in central-south Argentina and Chile. In this work, we describe a new species belonging to the L. petrophilus clade using an integrative approach that includes the analysis of morphological (lepidosis, morphometric, coloration and hemipenis characters) and molecular evidence (genetic distances and phylogeny). We provide information about the geological formation of the study area and the clade distribution, and present an extensive description of its natural history (including diet, habitat, behaviour, phytogeography, mode of life, and sympatric species). Additionally, we present a time divergence analysis of internal branches for all representatives of the L. elongatus group. This newly described species shows character states (morphological and molecular) that allow its clear distinction from the other members of the L. elongatus group, as well as from the remaining Liolaemus species. According to our results, the L. elongatus group originated during the Miocene, whereas the new species diverged from its sister taxon during the Pleistocene.